PRedictive Intelligence in MEdicine : first International Workshop, PRIME 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Proceedings /: first International Workshop, PRIME 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Proceedings. (2018) - Unknown
No abstract available